Pengaruh Perceived External Prestige, Pay Satisfaction, dan Work Pressure Terhadap Employee Performance PT Pelindo Daya Sejahtera - Iasa Nur Firdausi; Nirawati, Lia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In increasing the likelihood of success, the company needs to maintain the good image of the company in order to increase the confidence of external parties in fulfilling and carrying out tasks properly. Researchers tested one of the well-known companies in East Java, PT Pelindo Daya Sejahtera as the object of research because the company has a positive image, good salary satisfaction, and work pressure that can be used as parameters in the research to analyze the effect of perceived external prestige, pay satisfaction, and work pressure on employee performance at PT Pelindo Daya Sejahtera. In this study, quantitative descriptive methods were used in this study. The data collection method in this study was carried out by observation, interviews, questionnaires, and literature studies and data processing was carried out with the help of the SPSS 25 program. So obtained the results of the f test that has been carried out in this study then it can be concluded that perceived external prestige (X1), pay satisfaction (X2), and work pressure (X3) together have a significant effect on employee performance (Y) at PT Pelindo Daya Sejahtera. In addition, the results of the t test explain that perceived external prestige (X1) and work pressure (X3) have a significant effect on employee performance (Y) at PT Pelindo Daya Sejahtera. While the variable pay satisfaction (X2) does not have a significant effect on employee performance (Y) at PT Pelindo Daya Sejahtera.